If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2n + -7) + 7(4 + -2n) = 0 Reorder the terms: 3(-7 + 2n) + 7(4 + -2n) = 0 (-7 * 3 + 2n * 3) + 7(4 + -2n) = 0 (-21 + 6n) + 7(4 + -2n) = 0 -21 + 6n + (4 * 7 + -2n * 7) = 0 -21 + 6n + (28 + -14n) = 0 Reorder the terms: -21 + 28 + 6n + -14n = 0 Combine like terms: -21 + 28 = 7 7 + 6n + -14n = 0 Combine like terms: 6n + -14n = -8n 7 + -8n = 0 Solving 7 + -8n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -8n = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -8n = 0 + -7 -8n = 0 + -7 Combine like terms: 0 + -7 = -7 -8n = -7 Divide each side by '-8'. n = 0.875 Simplifying n = 0.875
| x^2-6x+20=0 | | 124-6x=21x+16 | | 3/2(5x-2)=x | | 3(x+4)+2(5x+2)= | | 6x+7+3x+1= | | -4x+5=5-4x | | -3y+6=-4y+7 | | 7xy-xy+3xy= | | 4w-5+9w+2= | | -4+5=5-4x | | 20-x=10x-2 | | 3x-(2x+9)=4x-27 | | 87-5x=40x+22 | | x+(x+27)+(3x-24)=633 | | -14-4x=13-7x | | 4a^2-9b^2=0 | | 4m^2-9k^2=0 | | 11n-14= | | 2x-6=8x-24 | | x+7(4)=16 | | 12k+9=0 | | 9+6r-4=9r+14-2r | | m^4-4m^3+7m^2-4m+6=0 | | m^7+m^5= | | 6(6v+6)=1+6v | | 12-8x=39-15x | | 2t+11t=104 | | 6x+7=-199-8x | | 14=20-2x | | 30k+10=18k+22 | | 49*7= | | 9d+18=2d+18 |